Controllable Synthesis of Ultrathin Defect‐Rich LDH Nanoarrays Coupled with MOF‐Derived Co‐NC Microarrays for Efficient Overall Water Splitting. Issue 29 (26th June 2022) - Guo, Tongtian; Chen, Liyu; Li, Yingwei; Shen, Kui
Abstract: Water electrolysis has attracted immense research interest, nevertheless the lack of low‐cost but efficient bifunctional electrocatalysts for both hydrogen and oxygen evolution reactions greatly hinders its commercial applications. Herein, the controllable synthesis of ultrathin defect‐rich layered double hydroxide (LDH) nanoarrays assembled on metal‐organic framework (MOF)‐derived Co‐NC microarrays for boosting overall water splitting is reported. The Co‐NC microarrays can not only provide abundant nucleation sites to produce a large number of LDH nuclei for favoring the growth of ultrathin LDHs, but also help to inhibit their tendency to aggregate. Impressively, five types of ultrathin bimetallic LDH nanoarrays can be electrodeposited on the Co‐NC microarrays, forming desirable nanoarray‐on‐macroarray architectures, which show high uniformity with thicknesses from 1.5 to 1.9 nm. As expected, the electrocatalytic performance is significantly enhanced by exploiting the respective advantages of Co‐NC microarrays and ultrathin LDH nanoarrays as well as the potential synergies between them. Especially, the optimal Co‐NC@Ni2 Fe‐LDH as both cathode and anode can afford the lowest cell voltage of 1.55 V at 10 mA cm ‐2, making it one of the best earth‐abundant bifunctional electrocatalysts for water electrolysis. This study provides new insights into the rational design of highly‐active and low‐cost electrocatalysts and facilitates their promising applications in the fields of energy storage and conversion. Abstract : A two‐electrode system for overall water splitting based on ultrathin defect‐rich layered double hydroxide (LDH) nanoarrays strongly coupled with metal‐organic framework (MOF)‐derived Co‐NC microarrays as bifunctional catalysts is developed. Such a unique nanoarray‐on‐microarray architecture can provide rich catalytic sites, good conductivity, and short ion diffusion paths, all of which contribute to enhancing the electrocatalytic performances.